ENVIRONMENTAL EDUCATION AS A FUNDAMENTAL PILLAR OF SUSTAINABLE SOLID WASTE MANAGEMENT: AN INTEGRATIVE APPROACH TO SOCIAL AND ENVIRONMENTAL CHANGE - ALBA JOSEFA VARGAS BUITRAGO, CARLOS ALBERTO AMAYA CORREDOR, JOSÉ LUIS BAUTISTA GONZÁLEZ (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
In a world in which the generation of solid waste is increasing by leaps and bounds, the proper management of this waste is a decisive challenge for society. Lack of environmental awareness, excessive waste generation, and inadequate waste management and disposal have a negative impact on the environment and public health. In this context, environmental education emerges as a necessary tool to encourage sustainable practices and promote a paradigm shift in the society-environment relationship. The methodology used in the research was descriptive with a qualitative approach, under a deductive method, in which, an exhaustive bibliographic review was carried out in scientific databases, using keywords such as “environmental education”, “waste management”, “sustainability” and “behavioral change”. Published articles were selected that analyzed the subject strictly and provided empirical evidence on the impact of environmental education on waste management. The review of the information showed a general consensus on the importance of environmental education as a differentiating element for effective and sustainable waste management. The studies analyzed highlight, among other benefits, the promotion of social responsibility, greater environmental knowledge and awareness, and the adoption of responsible habits. It is concluded that environmental education is a transcendental pillar for effective and sustainable waste management. Its implementation in different contexts is crucial to encourage behavioral change, promote citizen participation and build a more environmentally responsible society.